Chicken Egg Yolk Antibody (IgY) Protects Mice Against Enterotoxigenic Escherichia coli Infection Through Improving Intestinal Health and Immune Response - Han, Shuaijuan; Wen, Yang; Yang, Fengfan; He, Pingli (Frontiers in Cellular and Infection Microbiology, 2021)
Chicken egg yolk antibody (IgY), considered as a potential substitute for antibiotics, has been used for preventing pathogens infection in food, human and animals. This study investigated effects of IgY on growth, adhesion inhibitory and morphology of enterotoxigenic Escherichia coli (ETEC) K88 in vitro, and evaluated the protective effects of IgY on intestinal health and immune response of mice infected with ETEC in vivo. Sixty pathogen-free C57BL/6J (4-6 weeks of age) mice were divided into six treatments: control (neither IgY nor ETEC infection), ETEC infection, ETEC-infected mice treated with 250 μL of high-dose (32 mg/mL), medium-dose (16 mg/mL) or low-dose (8 mg/mL) anti-ETEC IgY, or ETEC-infected mice treated with 250 μL of non-specific IgY (16 mg/mL). Anti-ETEC IgY inhibited ETEC growth, reduced adherence of ETEC to intestinal epithelial cells J2 and damaged the morphology and integrity of ETEC cell. Oral administration of anti-ETEC IgY effectively ameliorated ETEC-induced clinical signs, reduced ETEC colonization and intestinal permeability, alleviated inflammatory response through reducing the production and expression of proinflammatory cytokines, improved intestinal morphology, and inhibited excessive activation of the mucosal immune response of challenged mice. The overall protective effects of high-dose and medium-dose anti-ETEC IgY against ETEC infection were more effective. These results suggest that anti-ETEC IgY may function as a promising novel prophylactic agent against enteric pathogens infection.